2015
DOI: 10.1075/ml.10.2.04coo
|View full text |Cite
|
Sign up to set email alerts
|

Lexical access in L2

Abstract: Previous research on phonological priming in a Lexical Decision Task (LDT) has demonstrated that second language (L2) learners do not show inhibition typical for native (L1) speakers that results from lexical competition, but rather a reversed effect – facilitation (Gor, Cook, & Jackson, 2010). The present study investigates the source of the reversed priming effect and addresses two possible causes: a deficit in lexical representations and a processing constraint. Twenty-three advanced learners of Russian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…Chrabaszcz & Gor, 2014). In such cases, words sound alike to L2 listeners, even though they are easily distinguishable to native (L1) listeners (for further discussion, see especially Broersma & Cutler, 2011;Cook & Gor, 2015;Darcy et al, 2013).…”
Section: Difficult Sounds In L2 Speech Perceptionmentioning
confidence: 99%
“…Chrabaszcz & Gor, 2014). In such cases, words sound alike to L2 listeners, even though they are easily distinguishable to native (L1) listeners (for further discussion, see especially Broersma & Cutler, 2011;Cook & Gor, 2015;Darcy et al, 2013).…”
Section: Difficult Sounds In L2 Speech Perceptionmentioning
confidence: 99%
“…For example, hearing the onset pa-in "panda" activates "pencil" for Dutch listeners (Weber & Cutler, 2004) and the onset r-in "rocket" activates "locker" for Japanese listeners (Cutler, Weber, & Otake, 2006). Phonolexical ambiguity can also occur in quite distinct words due to weak and fuzzy form-to-meaning mappings in the L2 (e.g., "quarrel"-"squirrel"; Cook & Gor, 2015;Cook, Pandža, Lancaster, & Gor, 2016).…”
mentioning
confidence: 99%
“…However, a lack of inhibition, and even facilitation was reported for advanced L2 learners of Russian with L1 English. Importantly, nonnative facilitation was observed for less familiar low-frequency primes, which is consistent with weaker lexical competitors having underdifferentiated, or fuzzy phonolexical representations (Cook & Gor, 2015; Gor & Cook, unpublished manuscript; Gor, Cook & Jackson, 2010). 4 In particular, Cook and Gor (2015) report overall inhibition in a LDT with phonological priming in advanced L2 learners of Russian.…”
Section: Less Familiar Nonnative Words Have Weak Underdifferentiatedmentioning
confidence: 73%
“…Importantly, nonnative facilitation was observed for less familiar low-frequency primes, which is consistent with weaker lexical competitors having underdifferentiated, or fuzzy phonolexical representations (Cook & Gor, 2015; Gor & Cook, unpublished manuscript; Gor, Cook & Jackson, 2010). 4 In particular, Cook and Gor (2015) report overall inhibition in a LDT with phonological priming in advanced L2 learners of Russian. However, when the reaction time data were reanalyzed separately for unknown, well-known and recognizable primes based on the results of a separate translation task, the trials with well-known primes continued to show inhibition, while the trials with recognizable primes showed a tendency to facilitation.…”
Section: Less Familiar Nonnative Words Have Weak Underdifferentiatedmentioning
confidence: 73%
See 1 more Smart Citation